Adapters in lymphocyte signalling - Leo, Albrecht; Schraven, Burkhart (Current opinion in immunology, 2001)
Adapter proteins are well recognised as important molecular switches connecting immunoreceptors with intracellular signalling pathways. However, recent data suggest that homeostasis within the lymphatic system also depends on the coordinated activities of negative regulatory adapter proteins. These prevent activation of lymphocytes in the absence of externally applied signals and regulate termination/limitation of ongoing immune responses via different mechanisms.
Gesehen am 19.02.2021